THE ATTITUDE OF VOCATIONAL STUDENTS TOWARD LEARNING SPEAKING IN EFL CONTEXT - Eryanika Rahma Kurniarizki; Aryati Prasetyarini (University of Muhammadiyah Malang, 2023)
This study aimed to determine whether vocational students in grades 10 and 11 have attitude problems toward learning to speak, identify the causes of the problems in learning to speak and describe how they perceive their learning to speak. This study employed a mixed method, with descriptive statistics to analyze quantitative data and a descriptive interactive technique to analyze the qualitative data. Participants who voluntarily filled in the questionnaire were 109 students and six students as interview participants. Besides that, an English teacher voluntarily became the informant to be interviewed. Data was collected through questionnaires and interviews. The results showed that students' behavior in speaking and feelings of emotional attitude is quite good. However, the students' cognitive attitude to acquire and apply knowledge of speaking English is not good. This is due to low self-confidence when answering or expressing opinions in English. They were worried that the difference between pronunciation and writing would lead to mistakes when speaking English. TS vocational students' perceptions of learning to speak are basically like this learning. However, the lack of understanding of the material being taught causes boredom during the learning process.